2006
DOI: 10.1038/emm.2006.66
|View full text |Cite
|
Sign up to set email alerts
|

An alternatively spliced form of Met receptor is tumorigenic

Abstract: The Met tyrosine kinase receptor is a widely expressed molecule, which mediates pleiotropic cellular responses following activation by its ligand, hepatocyte growth factor/scatter factor (HGF/SF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…However, gain-of-function mutations to c-Met are not exclusive to the tyrosine kinase domain. The juxtamembrane domain is critical for the metabolism of c-Met because mutations in this domain inhibit ubiquitylation, ultimately increasing receptor insertion into the cell membrane (Lee et al, 2006a). The ability of c-Met siRNA treatment of tumor cells to suppress growth and metastasis further highlights the critical role played by c-Met in cancer cell behavior (Corso et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gain-of-function mutations to c-Met are not exclusive to the tyrosine kinase domain. The juxtamembrane domain is critical for the metabolism of c-Met because mutations in this domain inhibit ubiquitylation, ultimately increasing receptor insertion into the cell membrane (Lee et al, 2006a). The ability of c-Met siRNA treatment of tumor cells to suppress growth and metastasis further highlights the critical role played by c-Met in cancer cell behavior (Corso et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HGF/c-Met signaling activates several cellular responses, such as proliferation, migration, invasion, and scattering, which are essential for transition to a metastatic phenotype. Many studies have shown that HGF/c-Met activation augments mitogenic and invasive activity in ovarian, glioma, gastric, and lung carcinomas (Ma et al, 2003;Lee et al, 2006a). Elevated c-Met expression and/or activation are generally correlated with a poor prognosis in many malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The direct and irreplaceable relationship between Y1003 and Cbl binding was clearly demonstrated when the replacement of Y1003 by a phenylalanine residue abrogated the ubiquitination (15)(16)(17). Thus, in the absence of the JM domain, Cbl is unable to initiate the ubiquitination process of Met and therefore, the receptor remains constitutively active acquiring eventually an oncogenic activity (18,19).…”
Section: Discovery and Oncogenic Potential Of Met Exon 14 Alternativementioning
confidence: 99%
“…These MET ex14 alterations were shown to promote RNA-splicingbased skipping of MET exon 14, which results in activation of MET kinase activity through a unique mechanism. The portion of the protein encoded by exon 14, most prominently Y1003 in a DpYR motif, is required for effi cient recruitment of the ubiquitin ligase CBL, which targets MET for ubiquitinmediated degradation (16)(17)(18). Loss of MET exon 14 maintains the reading frame and leads to increased MET stability and prolonged signaling upon HGF stimulation, leading to increased oncogenic potential ( 19,20 ).…”
Section: Introductionmentioning
confidence: 99%